Peran Kepuasan Kerja dalam Memediasi Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan - Suwandana, Suwandana; Made, I Gusti (Journal of Comprehensive Science, 2025)
The increasingly fierce competition in the development of the business world encourages companies to optimize employee performance in order to achieve the desired goals. Product and service innovation, as well as effective human resource management are important to increase the company's competitiveness. This study examines the influence of the work environment on employee performance through the role of job satisfaction variables as a mediator. This study uses an associative quantitative approach, with a research sample of 100 samples calculated using the Slovin formula. The research data is primary data through interviews and questionnaire distribution. The data analysis techniques used in this study are path analysis with SPSS, sobel test, and VAF test. The results of this study show that the work environment has a positive and significant effect on employee performance, the work environment has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction significantly mediates the influence of the work environment on employee performance.